GEOGRAPHY OF FRENCH TOURISM - Axmedova Mahliyo; Xomidov Samandar Azamatjon o'g'li; Nodirbekov Davronbek Nodirbek og'li (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Annotation: France is one of the most popular tourist destinations in the world, attracting millions of visitors each year. The country boasts a rich cultural heritage, stunning landscapes, and diverse regions that offer unique experiences. From the sun- kissed beaches of Côte d'Azur to the snow-capped mountains of the Alps, France has everything a tourist could ask for.